People's perception on children's freedom of speech / Natasha Aryanie Ag Matahir and Nurfatin Maisarah Norhaizat - Ag Matahir, Natasha Aryanie; Nurhaizat, Nurfatin Maisarah (2018)
Children's Freedom of Speech has been seen differently here especially in Malaysia. It is become a culture that a children should follow the rule and regulation set out in the family. Thus, children rarely had given the opportunity to speak up for their rights and freely in decision making. There are some situation that children are not allowed to enter any platform to increase their confidence and self-esteem. Therefore, this study examines the people's perception on children freedom of speech and how the parental behavior determines the people's perception. By understanding the children development, is there exist of opportunity for people's changes their perception toward children freedom of speech.